Strikes as forest fires: Chicago and Paris in the late nineteenth century - Biggs, M (University of Chicago Press, 2005)
Historians have persistently likened strike waves to wildfiles, avalanches, and epidemics. These phenomena are characterized by a power-law distribution of event sizes. This kind of analysis is applied to outbreaks of class conflict in Chicago from 1881 to 1886. Events are defined as individual strikes or miniature strike waves; size is measured by the number of establishments or workers involved. In each case, events follow a power law spanning two or three orders of magnitude. A similar pattern is found for strikes in Paris from 1890 to 1899. The 'forest fire' model serves to illustrate the kind of process that can generate this distribution.